PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING : (STUDI KASUS PADA OPERATOR PT MULTI TECHNIC INSULATION) - Adela Dwi Meliyanti (2022)
This study aims to determine and prove the direct and indirect effect of workload and compensation on turnover intention through job satisfaction as an intervening variable. This research is a quantitative research with a sample of 59 employees of PT Multi Technic Insulation operator with sampling technique using saturated sampling technique. The analytical technique applied in this research is descriptive analysis technique and inferential analysis with the help of the SmartPLS 3.0 test tool. Meanwhile, the hypothesis test is t test using a significance level of 5% (0.05). the results of this study indicate (1) workload has a positive and significant effect on turnover intention; (2) Compensation has a positive and significant effect on turnover intention; (3) Job satisfaction has a positive and significant effect on turnover intention; (4) Workload has no positive and insignificant effect on turnover intention through job satisfaction, and (5) Compensation has no positive and insignificant effect on turnover intention through employee job satisfaction.